Integrating design thinking and meta-analysis to identify effective technology enhanced learning media for mathematical problem solving in the industry 4.0 Era - Anjani, Windi; Muhtarom; Supandi (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to integrate Design Thinking and meta-analysis to systematically identify effective technology-enhanced learning media for improving students’ mathematical problem-solving skills in the Industry 4.0 era. Method: An exploratory mixed-method design was employed. The qualitative phase adopted the Design Thinking framework, focusing on the empathize, define, and ideate stages to analyze the needs of 98 junior high school students and 5 mathematics teachers through questionnaires, interviews, and classroom observations. Based on the ideation outcomes, potential instructional solutions were identified. To strengthen the validity of these proposed solutions, a meta-analysis of five relevant empirical studies was conducted using JASP software to estimate pooled effect sizes, heterogeneity, and prediction intervals. Findings: The Design Thinking process identified three promising technology-enhanced learning media: Augmented Reality (AR), Nearpod applications, and digital booklets. The meta-analytic results indicated a moderate pooled effect size (ES = 0.447, p < 0.05), suggesting a statistically significant positive influence on students’ mathematical problem-solving skills. The prediction interval further demonstrated the potential applicability of these media across diverse educational contexts. Significance: This study contributes a structured, evidence-informed framework that integrates user-centered design and quantitative synthesis to guide instructional technology selection in mathematics education aligned with Industry 4.0 demands.